2003
DOI: 10.4012/dmj.22.137
|View full text |Cite
|
Sign up to set email alerts
|

Development of Metal-resin Composite Restorative Material Part 5: Evaluation of the Bonding between Ag-Sn Particle and 4-META Coupling Agent of the Metal-resin Composite

Abstract: This study evaluated the oxide characteristics on a Ag-Sn particle surface modified by acid and heat in order to understand the bonding mechanism. Nine different Ag-Sn particles including standard Sn, SnO and SnO2 were evaluated by X-ray Photoelectron Spectroscopy (XPS). The particles were also used for preparing the composite to test the flexural properties following the ISO4049.A high correlation between flexural strength of the composites and Sn3d binding energy of their filler particles was found.Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In their initial attempts at developing metal-resin composites, Hirano et al 8) and Kakuta et al 13) reported that the highest flexural strengths were 55.9 MPa and 61.3 MPa, respectively. Subsequently, they reported much better values (71 MPa and 102.4 MPa, respectively) by modifying the filler surface treatment as shown in later papers 9,14) . Thus, remarkable improvement in mechanical properties can be expected by modifying the filler surface treatment in future studies.…”
Section: Discussionmentioning
confidence: 97%
“…In their initial attempts at developing metal-resin composites, Hirano et al 8) and Kakuta et al 13) reported that the highest flexural strengths were 55.9 MPa and 61.3 MPa, respectively. Subsequently, they reported much better values (71 MPa and 102.4 MPa, respectively) by modifying the filler surface treatment as shown in later papers 9,14) . Thus, remarkable improvement in mechanical properties can be expected by modifying the filler surface treatment in future studies.…”
Section: Discussionmentioning
confidence: 97%
“…The chromium content in the Co-Cr alloy produces an oxide layer at room temperature which can enhance chemical bonding with . According to Urapepon et al 22) , they reported that 4-META has an ability to bond metal oxide on Ag-Sn filler particle to polymeric matrix in a metal-resin composite. Moreover, this study also reported in depth that different oxide form (SnO and SnO 2) produced different adhesion ability of 4-META.…”
Section: Discussionmentioning
confidence: 99%
“…In their initial attempts at developing metal-resin composites, Hirano et al 8) and Kakuta et al 16) reported that the highest flexural strengths were 55.9 MPa and 61.3 MPa, respectively which were almost the same as that obtained in the present study. Subsequently, they reported much better values by modifying the methods in later papers 9,19) . As suggested in Fig.…”
Section: )mentioning
confidence: 99%